Philosophical Issues in Tibetan Folk Medisine - Yuldasheva L. S., (European Journal of Life Safety and Stability (2660-9630), 2024)
The article examines the main concepts of Buddhist philosophy and their connection with the theory of Tibetan medicine. The philosophy of Buddhism served as the ideological basis for the medical tradition of Tibet, having formed its ideas about the nature of man, diseases and specific approaches and methods of treatment, as well as having determined its ultimate supreme goal.